The spread and control of HIV/AIDS infection using the SIR model / Wan Nurul Husna Wan Nordin … [et al.] - Wan Nordin, Wan Nurul Husna; Abdul Manaf, Zati Iwani; Ruzali, Fatin Idayu; Zulkefri, Aimie Aqilah; Yahya, Ain Syafiqah (Faculty of Computer and Mathematical Sciences, Universiti Teknologi MARA Cawangan Kelantan, 2022)
This research discussed the SIR model and how it models the spread of HIV/AIDS in Malaysia. The data used were collected from HIV/AIDS Asia Pacific Research Statistical Data. Several parameters and initial conditions need to be assumed as research limitations such as value of parameter γ and the disease transmission rate, β. The aim of this research is to calculate the basic reproductive number, R0. The basic reproductive number R0, is a measure of the communicable rate of the virus, reflecting the average number of new infections caused by an infected individual in a completely unharmed population from any disease. Then, we applied a numerical solution method, which is Euler's method to predict the susceptible and infected cases. We plot the predicted susceptible and infected cases using Microsoft Excel. Based on the results and the discussion obtained, the transmission is likely to decrease and indicates that disease spread is under relatively reasonable control.